2008
DOI: 10.1016/j.psyneuen.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Diminished cortisol responses to psychosocial stress associated with lifetime adverse events

Abstract: These findings suggest that, at least in healthy young males, adverse childhood events are associated with changes in HPA-axis functioning. Longitudinal studies are needed to investigate whether the blunted cortisol response is a risk factor in the etiology of psychiatric disorders or rather reflects resiliency with regard to the development of psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
206
4
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(251 citation statements)
references
References 63 publications
31
206
4
10
Order By: Relevance
“…We observed a relative hypothalamuspituitary-adrenal axis hypo-reactivity in the group of adults with childhood trauma history, evidenced by lower ACTH and cortisol responses to acute stress exposure. This is in line with the majority of studies reporting dampened stress system activity associated with early adversity (Carpenter et al, 2007;Miller et al, 2007;Elzinga et al, 2008;Lovallo et al, 2011;Power et al, 2012), although the opposite has also been reported (Heim et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…We observed a relative hypothalamuspituitary-adrenal axis hypo-reactivity in the group of adults with childhood trauma history, evidenced by lower ACTH and cortisol responses to acute stress exposure. This is in line with the majority of studies reporting dampened stress system activity associated with early adversity (Carpenter et al, 2007;Miller et al, 2007;Elzinga et al, 2008;Lovallo et al, 2011;Power et al, 2012), although the opposite has also been reported (Heim et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…22 Furthermore, altered cortisol release patterns have been found in infants with disorganized attachment 23 and in adults with childhood emotional maltreatment. 24 2. Dissociation.…”
Section: Risk Mechanisms In Disorganized Attachmentmentioning
confidence: 99%
“…Currently the HPA axis appears to be involved in the response to early adverse life events in persons without psychiatric disorders. Elzinga et al [14] found that adverse childhood events in healthy young males are associated with changes in HPA axis function. This is similar to Carpenter et al [5], who found a diminished HPA axis in 23 healthy adults with maltreated childhood.…”
Section: Introductionmentioning
confidence: 99%